Urban Agrarian Reform for State Land Cultivators in the Special Capital Region of Jakarta - Manurung, Juwita; Fadli, Moh; Koeswahyono, Imam; Permadi, Iwan; Anditya, Ariesta Wibisono (INTERNATIONAL JOURNAL ON LANGUAGE, RESEARCH AND EDUCATION STUDIES, 2025)
Legal regulations in the Indonesian legal framework governing state land cultivators in urban areas remain contentious and require further legal examination. Agrarian reform efforts have largely focused on rural areas, even as the phenomenon of cultivators occupying state land in urban regions has significantly grown, creating social systems rooted in the lands they cultivate. These lands serve as their primary means of livelihood, places of social interaction, sites for familial continuity, and as long-term residences. Cultivators use the land without any legal ownership rights. Current legislation does not accommodate applications for the registration of land use rights for cultivators, leaving urban cultivators (in DKI Jakarta) without legal certainty or priority rights to apply for land rights. This legal void presents an inherent injustice to cultivators seeking priority rights over their cultivated land. Furthermore, the Job Creation Law, as framed by the government, reflects a latent capitalist ideology, reserving the right to apply for land-use rights solely for business actors (developers), thereby excluding cultivators themselves. This situation underscores the urgent need for a legal reformulation based on justice principles for the utilization of state land by cultivators in Indonesia, aiming to actualize agrarian reform in urban areas.